2013
DOI: 10.1117/12.2010656
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of dynamic performance of a prototype hybrid tuned mass damper under human excitation

Abstract: Current sport stadia designs focus mainly on maximizing audience capacity and providing a clear view for all spectators. Hence, incorporation of one or more cantilevered tiers is typical in these designs. However, employing such cantilevered tiers, usually with relatively low damping and natural frequencies, can make grandstands more susceptible to excitation by human activities. This is caused by the coincidence between the activity frequencies (and their lowest three harmonics) and the structural natural fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Moreover, based on the time history analyses of a single-DOF with a TMD system, it was observed that for large damping of the structure, the TMD did not give much response reduction. The problem of the TMD off-tuning (detuning) is also reported in (Setareh (2002); Shih and Sung (2021); Noormohammadi and Reynolds (2013); Setareh et al (2007); Maślanka (2019)). Gutierrez Soto and Adeli (2013) mentioned that, a disadvantage of PTMDs is that they can only be tuned in one frequency which is subject to uncertainty or it could change during ground motions.…”
Section: Hardware-related Limitationsmentioning
confidence: 72%
“…Moreover, based on the time history analyses of a single-DOF with a TMD system, it was observed that for large damping of the structure, the TMD did not give much response reduction. The problem of the TMD off-tuning (detuning) is also reported in (Setareh (2002); Shih and Sung (2021); Noormohammadi and Reynolds (2013); Setareh et al (2007); Maślanka (2019)). Gutierrez Soto and Adeli (2013) mentioned that, a disadvantage of PTMDs is that they can only be tuned in one frequency which is subject to uncertainty or it could change during ground motions.…”
Section: Hardware-related Limitationsmentioning
confidence: 72%
“…HMDs represent a class of TMDs with an added active control device . Like many active control systems, the active force of an HMD is usually determined by the selected control law and online measurement of the system responses, excitations, or both; therefore, an HMD is capable of adding an optimal force to the controlled structure in real time for earthquakes with diverse characteristics.…”
Section: Introductionmentioning
confidence: 99%